2016
DOI: 10.1109/tits.2016.2551780
|View full text |Cite
|
Sign up to set email alerts
|

Ship Collision Avoidance and COLREGS Compliance Using Simulation-Based Control Behavior Selection With Predictive Hazard Assessment

Abstract: Abstract-This paper describes a concept for a collision avoidance system for ships, based on model predictive control. A finite set of alternative control behaviors are generated by varying two parameters: offsets to the guidance course angle commanded to the autopilot, and changes to the propulsion command ranging from nominal speed to full reverse. Using simulated predictions of the trajectories of the obstacles and ship, the compliance with COLREGS and collision hazards associated with each of the alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
224
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(242 citation statements)
references
References 25 publications
0
224
0
1
Order By: Relevance
“…However, if it is apparent that the giveway vessel is not taking action to avoid collision, the stand-on vessel is required to apply actions to best avoid collision. Rule 8 is considered in [10] by limiting the possible actions, resulting in distinct observable actions. These rules are, however, seldom considered in the literature.…”
Section: The International Regulations For Preventing Collisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if it is apparent that the giveway vessel is not taking action to avoid collision, the stand-on vessel is required to apply actions to best avoid collision. Rule 8 is considered in [10] by limiting the possible actions, resulting in distinct observable actions. These rules are, however, seldom considered in the literature.…”
Section: The International Regulations For Preventing Collisionsmentioning
confidence: 99%
“…and can encode more sophisticated criteria for the behavior, for instance generating observable maneuvers which are optimal in a global sense. Examples of deliberate algorithms include rapidly-exploring random trees (RRT) [6], graph search algorithms such as A* and D* [7,8] and constrained nonlinear optimization [9,10]. A downside of deliberate algorithms is their computational complexity, which results in high computational requirements and possibly challenges for real-time implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemetron, which is Maritime Robotics’ research and development vessel was therefore prepared for a test week in the North Sea, from November 20 to 24, 2017. In close collaboration with the Norwegian University of Science and Technology (NTNU), Maritime Robotics equipped Telemetron with the model predictive control (MPC)‐based collision avoidance strategy described in Hagen, Kufoalor, Brekke, and Johansen () and Johansen, Perez, and Cristofaro (). Since its first implementation and deployment on the Telemetron vessel in 2016, the MPC strategy has been tested and refined through experimental field work consisting of several campaigns in the Trondheimsfjord in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Model predictive control (MPC), which combines path planning with on-line stability and convergence guarantees, is increasingly being applied to collision avoidance problem [27]. One significant study can be found in the work undertaken by Johansen [28], who applied MPC in the CAS of ship with a simple external environment. However in contrast to ordinary ships, considering that USVs have the characteristics of high speed and smaller volume, the CAS needs shorter computation times and stronger robustness.…”
Section: Introductionmentioning
confidence: 99%